Early-onset Cardiotoxicity assessment related to anthracycline in children with leukemia. A Prospective Study - Adriana Linares Ballesteros (Colombia Médica, 2021)
Background: Acute leukemias are the most frequent malignancies in children. Advances in treatment have improved the overall survival to 80%. Almost 10% of children with cancer develop clinical cardiac toxicity. Total anthracycline cumulative dose is a risk factor for early-onset cardiotoxicity.Objective: To describe the incidence of early-onset cardiotoxicity in children with acute leukemia treated with chemotherapy.Methods: A prospective descriptive study of patients >1 y and <18 years diagnosed with acute leukemia. Assessed with electrocardiograma, echocardiography, and blood biomarkers at diagnosis and during the follow-up.Results: 94 patients with acute lymphoblastic leukemia and 18 with acute myeloid leukemia were included. 20 patients (17.9%) developed early-onset cardiotoxicity. Statistically significant data was seen after anthracycline dose >150 mg/m2, between the first echocardiographic evaluation and posterior analyses in the left ventricular fraction ejection with Teicholz p 0.05, Simpson p 0.018 and GLS p 0.004. In this study, there was no relation between blood biomarkers and cardiotoxicity.Conclusions: Cancer therapeutic-related cardiac dysfunction is related to anthracycline cumulative dose. In this study, echocardiographic follow-up was useful to predict risk factors for early cardiac dysfunction.